2006
DOI: 10.1063/1.2165189
|View full text |Cite
|
Sign up to set email alerts
|

The hydration of Cu2+: Can the Jahn-Teller effect be detected in liquid solution?

Abstract: The long elusive structure of Cu͑II͒ hydrate in aqueous solutions, classically described as a Jahn-Teller distorted octahedron and recently proposed to be a fivefold coordination structure ͓Pasquarello et al., Science 291, 856 ͑2001͔͒, has been probed with x-ray-absorption spectroscopy by performing a combined theoretical and experimental analysis. Two absorption channels were needed to obtain a proper reproduction of the x-ray-absorption near-edge structure ͑XANES͒ region spectrum, as already observed in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
125
2
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 54 publications
16
125
2
2
Order By: Relevance
“…[14][15][16][17][18][19][20][31][32][33][34][35][36][37] Our calculations favor Cu(II)-water complexes with first-shell coordination number of five for clustes with eight to ten water molecules. Note the results of solvation calculations are sensitive to the selection of the copper solvation radius when Cu(II) ions are in contact with the solvent dielectric boundary.…”
Section: Structure and Energetics Of [Cu(h 2 O)mentioning
confidence: 99%
See 3 more Smart Citations
“…[14][15][16][17][18][19][20][31][32][33][34][35][36][37] Our calculations favor Cu(II)-water complexes with first-shell coordination number of five for clustes with eight to ten water molecules. Note the results of solvation calculations are sensitive to the selection of the copper solvation radius when Cu(II) ions are in contact with the solvent dielectric boundary.…”
Section: Structure and Energetics Of [Cu(h 2 O)mentioning
confidence: 99%
“…Conversely, Benfatto et al 18 and Frank et al 20 analyzed the XANES portions of the XAS spectra of Cu(II)-water solutions and concluded that a square-pyramidal model with one elongated axial water molecule provides a better fit of the data than a four-coordinate model or a Jahn-Teller axially elongated sixcoordinate model. More recently, Chaboy et al 19 used two absorption channels for simulating the EXAFS and XANES spectra of Cu(II)-water solutions. They concluded that the four-, five-, and six-coordinate structures are indistinguishable and are likely to dynamically coexist in solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Surprisingly, the coordination environment even for the simplest hydrated Cu(II) ion has been the subject of extensive debate in recent years. 21,[24][25][26][27][28][29][30][31][32] The most recent X-ray absorption studies (EXAFS and XANES) of aqueous solution of Cu(II), 26 as well as theoretical calculations performed by us 30 and others, 31,32 showed that the [Cu(aq)] 2+ ion can be represented as a five-coordinate square-pyramidal structure with one elongated axial water molecule. Despite the flexibility of the coordination geometry, Cu 2+ is one of the most strongly coordinated divalent transition metal ions.…”
Section: Introductionmentioning
confidence: 99%